Le Code civil : reflet des valeurs sociales d’un peuple - Crépeau, Paul-André (Assurances, 1982)
Without a doubt, the domineering social values of a society should be made perfectly clear by the Civil Code. Whether the rights relate to persons, families or successions, the right of property, of obligations, of civil responsibility one may rightfully expect to find in the C.C. the moral and economic concerns clearly expressed for the benefit of a population. Such is the message as rendered by the professor Paul-A. Crépeau, C.R., who assumed the direction of the Office of Revision of Civil Code. The past three decades have witnessed numerous changes and progress for the Quebec society. Indeed, this is why the Office presented to the Government, on June 20th, 1978, a major project reforming the Civil Code.